PENULISAN INKLUSIF DI PRANCIS: TANTANGANNYA BAGI POLITIK LINGUISTIK DAN TRANSMISI BAHASA PRANCIS DI INDONESIA - Merry Andriani (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
French society recently sparked a debate on the gender inclusive way of writing suggested by the Haut Conseil d’Egalité. Within the polemic of this new politic of linguistic, this article aims to describe the nature of the inclusive writing in French and why it is becoming the challenge to the politic of linguistic of French in Indonesia and its transmission in general. In order to expose these purposes, the sociolinguistic in critical approach is chosen to analyse the politic linguistic discourses aspects concerning this subject in diver French media. This research shows that despite the ideal purposes of inclusive writing system in French, there are a great potentiality that this new politic of linguistic will risk the transmission of French language in Indonesia. The difficulty is due to the complexity in the gender differentiation on the writing system adding a difficulty to the French learning which already well reputed as a difficult language to learn by the Indonesian public. The second problem is the uncertainty way of reading the new words using the median points, putting language instructors also in difficulty within their didactical task.